TINDAKAN PETANI SAWIT DALAM PEREMAJAAN KEBUN KELAPA SAWIT PLASMA DI DESA BUKIT JAYA KECAMATAN UKUI KABUPATEN PELALAWAN - Dita Purnama Wulan; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the village of Bukit Jaya Subdistrict Ukui Pelalawan District. The purpose of this research is to know the farmers ' survival strategy after conducting a rejuvenation of the palm groves of the Plasma in the village of Bukit Jaya Subdistrict Ukui Pelalawan District. The topic of this research focus is the Act of Palm farmers in palm groves Plasma rejuvenation in the village of Bukit Jaya Subdistrict Ukui Pelalawan District. Sample determination techniques in simple random sampling, and set the number of samples as many as 70 people. The author uses descriptive quantitative methods and instruments of data are observation, question form and documentation. The study found that in doing the replanting of Palm, there are several actions taken in society. namely as follows: follow the socialization of Replanting Of PT Asian Agri. Research found that 100% of the respondents (70 people) follow sosialiasai on replanting held by PT Asian Agri, conducting Deliberations with fellow Palm Farmers, 91.4 % of respondents (64 persons) conducts the deliberations with fellow farmers oil palm replanting done before, planning After Replanting, researchers found that 71.4% of respondents (50 people) have plan of looking for another job After replanting oil palm groves. Keywords: Farmers, Social Action, Palm Groves Plasma Rejuvenation